Optimization of Mrs. Salimah's Terasi Udang Products - Rosyidi, Rosyidi (Communautaire: Journal of Community Service, 2022)
Assistance to a micro business unit needs to be carried out, for improving the quality and quantity of the product, the development and progress will determine the economy of the local community, because the development of a production has led to good economic community. The development of a product can certainly be realized through various systematic and directed steps from the manufacturing process. The community service that has been carried out in Nepa, Sampang Regency is an assistance to the production of Terasi Udang Bu Salimah. The assistance is carried out in 4 aspects; production quality, production quantity, management and marketing. This assistance has measurable results, the development of the terasi packaging, becoming more attractive, and can reach a wider market, with good management. Based on good management can increase the quantity of production. In this community service, using the ABCD method, because the asset or potential existed in the community, the subject of this service provides assistance, where with this assistance, the community moves themselves in a direction towards their economic progress.